Nutritional assessment and antioxidant potential of selected meat types consumed in Owhelogbo, Delta State, Nigeria - J. O. Owheruo; G. I. Edo; P. O. Akpoghelie; A. O. Faturoti; E. F. Isoje; U. A. Igbuku; E. E.A. Oghroro; D. S. Ahmed; E. Yousif; Kh. Zainulabdeen; A. A. Mohammed; A. E.A. Essaghah; et al. (Теория и практика переработки мяса, 2025)
The present study aims at evaluating the nutritional value and antioxidant potential of various meat types (beef, pork, chicken, catfish and snails) consumed in Owhelogbo, community in Isoko Local Government, Delta State, Nigeria. The different meat samples were analyzed for nutritional composition and antioxidant properties. The results obtained show that the protein content varied from 20.09 to 61.74%, while the fat content varied from 2.00 to 12.08%. The calcium content ranged from 10.30 to 143.73 mg/100 g, while the phosphorous content ranged from 100.85 to 300.11 mg/100g. The linoleic acid content was in a range from 10.91 to 29.54%, while the linolenic acid content ranged from 0.84 to 5.53%. The content of vitamin A and vitamin D varied from 4.61 to 110.69 µg/100g and 2.15 to 18.05 µg/100g, respectively. The DPPH free radical scavenging ability and FRAP inhibitory activities of the different meat types ranged from 50.84 to 65.64% and 0.88 to 1.59%, respectively. The levels of high density lipoprotein and low density lipoprotein were in a range from 13.34 to 21.90 mg/dL and 2.30 to 5.59 mg/dL, respectively. The level of low density lipoprotein was the lowest in snail meat (SN), which suggests that it may be useful in managing obesity and preventing disorders linked to lipids. Consequently, the results conclude that snail meat may be a more valuable and innovative source of animal protein than beef, pork, chicken, and catfish.